(untitled) (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2025)
The objective of the research was to establish omnichannel communication strategies to attract new consumers to the Graduate Unit at the Technical University of Ambato. From a methodological point of view, a non-ex- perimental qualitative cross-sectional approach was used, applying interviews with the coordinators of the Graduate Units from various faculties of the institution to gather their opinions, perceptions, and experiences regarding the process of attracting new students. The data collected were processed using the ATLAS.ti tool to identify the most significant dimensions and categories of the study. The main findings revealed the need to implement integrated omnichannel communication strategies, such as a service desk, a chatbot, a community manager, and an exclusive call center for the Graduate Units, as a response to the needs and expectations of the new consumer. Finally, the study revealed the pressing need to recruit specialized marketing personnel and to train the current staff to optimize information management and social media advertising.